Penerapan Metode Pembelajaran Kooperatif Snowball Throwing dalam Meningkatkan Hasil Belajar Peserta Didik Kelas VIII C pada Mata Pelajaran Pendidikan Agama Islam - Surani Surani; Imaniar Bahtiar; Abd. Rauf Assegaf (Universitas Muslim Indonesia, 2022)
Understanding education briefly means formal education whose learning methods are carried out within the scope of formal schools, formal schools are limited by teaching materials, atmosphere, and the level of education to be taken. Using this brief understanding, it means that education is limited, namely where education takes place when it is carried out, subject matter, goals to be achieved, and scope of activities. The following article discusses the use of the snowball throwing cooperative learning method to improve student achievement in the PAI class at SMP Negeri 2 Burau. The main problem that needs to be solved is whether the snowball throw method of cooperative learning for class VIII students of SMP Negeri 2 Burau in East Luwu can improve their learning outcomes. The data processing methodology used is Classroom Action Research, with a focus on data analysis for Class VIII C consisting of 27 students, data processing procedures, and data analysis instruments. The two-month study begins on March 22 and ends on May 22, 2022. On average there are 3 meetings per cycle, but on average there is only one meeting per cycle, so there are 7 meetings in total. And the KKM level monitored in schools is 75. The results of cooperative learning to throw snowballs in class VIII C increased from pre-class to level II. The average pre-cycle learning completeness is 52.59, and the incomplete category is 24 students or 88.88%, and 3 students complete or 11.11 percent. Then on the page, I, the percentage of students who successfully complete the course is 70.37, and the percentage of students who do not successfully complete the course is 12 or 44, or 55. Then, in Part II, the percentage of workers is 88.88, with around 23 workers in the Trained category (or 85.18%) and about 4 workers in the Untrained category (or 14.81%). The conclusion is that the application of the snowball throw type of cooperative learning method can help Islamic Religious Education subjects at SMP Negeri 2 Burau, East Luwu Regency improve the learning outcomes of the class.